1977
DOI: 10.2224/sbp.1977.5.1.157
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Delinquency: A Multi. Variate Examination of Eysenck's Theory With Scottish Delinquent and Non-Delinquent Boys

Abstract: The Eysenck Junior P.1. questionnaire was administered to groups of institutionalized and non-institutionalized delinquents and to non-delinquents. Scores were evaluated at scale and item level by discriminant analysis. A further analysis of discriminant items produced new, empirically validated dimensions which, reapplied to a discriminant function program, allowed examination of their relative effectiveness in the (posterior) prediction of group membership. Additional hypotheses from Eysenck's theory concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Zbog toga je teško utvrditi da li je dobijeni skor na mjerama ličnosti povezan sa kriminogenim ponašanjem ili sa institucionalizacijom (Romero et al 2001). Na primjer, postoje podaci da intenzitet dimenzije Ekstraverzija opada sa hapšenjem i smještanjem u ustanovu (Allsopp & Feldman, 1974;Forrest, 1977;Haapasalo, 1990).…”
Section: Diskusijaunclassified
“…Zbog toga je teško utvrditi da li je dobijeni skor na mjerama ličnosti povezan sa kriminogenim ponašanjem ili sa institucionalizacijom (Romero et al 2001). Na primjer, postoje podaci da intenzitet dimenzije Ekstraverzija opada sa hapšenjem i smještanjem u ustanovu (Allsopp & Feldman, 1974;Forrest, 1977;Haapasalo, 1990).…”
Section: Diskusijaunclassified
“…Drug use has been associated with criminality (Kaplan, 1995;Miller, Whitney, & Washousky, 1986;Newcomb, Galaif, & Carmona, 2001), victimization manifestation of inner tension may occur in anxiety or manic-depressive states (Cormier, 1966;De Coster, 2003;Forrest, 1977;Harrer & KoflerWestergren, 1986). Among women in drug treatment, their past victimization experiences have been identified as fundamental to their drug use and participation in illegal activities (Welle et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, past life events, including a negative family or childhood history, also may contribute to the risk of criminality (Arata, 2000;Arnold, Stewart, & McNeece, 2001;Chesney-Lind, 1997;L'Abate & Baggett, 1997;Nyamathi, Wenzel, Lesser, Flaskerud, & Leake, 2001;Welle et al, 1998;West, Williams, & Siegel, 2000). Depression has been associated with criminality and research has shown that criminal acts arising from a manifestation of inner tension may occur in anxiety or manic-depressive states (Cormier, 1966;De Coster, 2003;Forrest, 1977;Harrer & Kofler-Westergren, 1986). Among women in drug treatment, their past victimization experiences have been identified as fundamental to their drug use and participation in illegal activities (Welle et al, 1998).…”
Section: Introductionmentioning
confidence: 99%